Fit and female : - Coopersmith, Geralyn (John Wiley & Sons, 2006)
Coopersmith, resident fitness instructor on the Fine Living Channel's Simplify Your Life, has devised a fitness and nutrition plan to accommodate the needs of women of all shapes and sizes. Observing that "fitness is not one size fits all," Coopersmith divides her approach to address six basic body shapes: the endo-pear, endo-apple, meso-pear, meso-apple, ecto-pear and ecto-apple. Each shape, she claims, requires a customized workout and eating plan, though all incorporate components of a cardio workout, muscular fitness segment and flexibility training. For instance, the already slim ecto pear focuses on shaping muscles while maintaining weight and should not overdo aerobic exercise, while the bulkier meso-apple needs to zero in on cardio work to trim the waist and abs. Illustrated exercises are provided for each body type. Noting that "fitness must fit into a busy woman's life," Coopersmith modifies each sequence, offering a "bare minimum," "ideal" and "gung-ho" work out. While Coopersmith's methods are individualized, her message to all women is to give up their notion of a "Barbie body," work with what they have, steer clear of fad diets and eat healthfully. Perky and friendly, Coopersmith offers an accessible plan and outlook that many women will warm up to.